2020
DOI: 10.18502/cmm.6.2.2692
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal susceptibilities of six antifungal drugs against clinical Candida glabrata isolates according to EUCAST

Abstract: Background and Purpose: Candida glabrata is the second cause of candidiasis. The mortality rate of C. glabrata infections is about 40%; accordingly, it may be life threatening, especially in immunocompromised hosts. Regarding this, the current study was conducted to evaluate the regional patterns of the antifungal susceptibility of clinical C. glabrata isolated from the patients referring to the health centers located in Ahvaz, Iran. Materials and Methods: In this study, a total of 30 clinical strains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Only C. glabrata was resistant to terbinafine antifungal, whereas Candida albicans and Candida tropicalis were found to be terbinafine sensitive. Fatahinia et al (2020) reported that 80% of isolated C. glabrata strains were resistant to terbinafine antifungal drugs [87]. The resistance of candidal to terbinafine has been linked to a single missense mutation in the squalene epoxidase gene, resulting in amino acid substitutions [88].…”
Section: Synergistic Antifungal Efficiency Of the Biogenic Zno Nanopa...mentioning
confidence: 99%
“…Only C. glabrata was resistant to terbinafine antifungal, whereas Candida albicans and Candida tropicalis were found to be terbinafine sensitive. Fatahinia et al (2020) reported that 80% of isolated C. glabrata strains were resistant to terbinafine antifungal drugs [87]. The resistance of candidal to terbinafine has been linked to a single missense mutation in the squalene epoxidase gene, resulting in amino acid substitutions [88].…”
Section: Synergistic Antifungal Efficiency Of the Biogenic Zno Nanopa...mentioning
confidence: 99%
“…C. glabrata has emerged as an important nosocomial fungal pathogen associated with a high mortality rate, around 40%, comparable to the ones associated with C. albicans [ 57 ]. A likely contributor to this is increased resistance to antifungal agents, particularly azoles [ 50 , 54 , 55 , 58 , 59 ]. In addition, the prevalence of implant infections caused by fungal pathogens has dramatically increased over the last 10 years.…”
Section: Candida Glabratamentioning
confidence: 99%